The Longroiva and Vilariça Depressions: Two Narrow Tectonic Basins with Different Impacts on the Human Occupation - Daveau, Suzanne (2020)
The Longroiva and Vilariça are two small tectonic basins located in NE Portugal, close to the Douro valley, along the Bragança-Vilariça-Manteigas strike-slip fault, one of the largest tectonic structures in Portugal. The area has been focus of interest of geological and geomorphological research for several decades, mainly due to their rich heritage of Paleogene to Quaternary deposits that contribute to a better understanding of the regional evolution. It includes Paleogene to Miocene arkoses predating the genesis of the depressions and adjacent relief, coarser sediments, correlative of Neogene tectonics, and Late Pliocene to Quaternary fluvial terraces associated with reorganization of the drainage westwards to the Atlantic Ocean. In this chapter, the main geomorphological features of the two basins are presented, as well as a brief history of the research that has been conducted in last decades. Finally, the history of human occupation is presented and discussed in the framework of the regional geomorphology and geographical location.